Relieving acute pain (RAP) study: a proof-of-concept protocol for a randomised, double-blind, placebo-controlled trial - Thomas Scalea; Luana Colloca; Se Eun Lee; Meghan Nichole Luhowy; Nathaniel Haycock; Chika Okusogu; Soojin Yim; Nandini Raghuraman; Robert Goodfellow; Robert Scott Murray; Patricia Casper; Myounghee Lee; et al. (BMJ Open)
Introduction Physicians and other prescribing clinicians use opioids as the primary method of pain management after traumatic injury, despite growing recognition of the major risks associated with usage for chronic pain. Placebos given after repeated administration of active treatments can acquire medication-like effects based on learning mechanisms. This study hypothesises that dose-extending placebos can be an effective treatment in relieving clinical acute pain in trauma patients who take opioids.Methods and analysis The relieving acute pain is a proof-of-concept randomised, placebo-controlled, double-blinded, single-site study enrolling 159 participants aged from 18 to 65 years with one or more traumatic injuries treated with opioids. Participants will be randomly assigned to three different arms. Arm 1 will receive the full dose of opioids with non-steroidal anti-inflammatory drugs (NSAIDs). Arm 2 will receive the 50% overall reduction in opioid dosage, dose-extending placebos and NSAIDs. Arm 3 (control) will receive NSAIDs and placebos. The trial length will be 3 days of hospitalisation (phase I) and 2-week, 1-month, 3-month and 6-month follow-ups (exploratory phase II). Primary and secondary outcomes include feasibility and acceptability of the study. Pain intensity, functional pain, emotional distress, rates of rescue therapy requests and patient-initiated medication denials will be collected.Ethics and dissemination All activities associated with this protocol are conducted in full compliance with the Institutional Review Board policies and federal regulations. Publishing this study protocol will enable researchers and funding bodies to stay up to date in their fields by providing exposure to research activity that may not otherwise be widely publicised.Date and protocol version identifier 3/6/2019 (HP-00078742).Trial registration number NCT03426137.